Language impairment and psychopathology in infants, children, and adolescents - Cohen, Nancy J., 1941-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2001)
There is a high correlation between language impairment and a range of psychological disorders in children and adolescents. This book describes and discusses this relationship, its etiology and consequences for the child, and its treatment.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Language disorders in children; Language disorders in children -- Complications; Language disorders in adolescence; Language disorders in adolescence -- Complications; Child psychopathology; Adolescent psychopathology; Comorbidity; Electronic books